AN APPRAISAL ON NIDANA PANCHAKA OF SHWASA ROGA - Sphoorthi, *Y Sharada; Dr, Ajantha (International Journal of Ayurveda and Pharma Research, 2017)
A detailed explanation on Shwasa roga can be traced in Ayurveda literature. This article is based on review on Nidana panchaka of Shwasa roga from Ayurvedic text such as Charaka samhitha, Sushruta Samhita, Astanga Hrudaya, Astanga Sangraha and Madhava nidana along with commentaries. Shwasa roga is characterized predominantly with difficulty in breathing. Majority of Nidanas are Vata and Kapha janaka hetus. These Nidanas causes Kapha Prakopa causing obstruction to movement of Vata resulting in Shwasa kruchratha manifesting as Shwasa roga. Prana and Udakavaha srotas are chiefly involved in pathogenesis. Manifestation of Prana vayu vilomatva, Anaha and Parshwashoola are important Poorva roopa. Five types of Shwasa may be clearly differentiated based on the following pathognomonic symptoms. Urdhwa shwasa manifest with Deergha shwasana and Urdhwa dristi. Maha shwasa presents with Ucchai shwasananam-mattha hrushabha iva and Vivruthaksha. Chinna shwasa presents with Vicchinna shwasa and Vipluthaksha. Kshudra shwasa presents with mild self limiting symptoms that do not interfere in daily activities. Tamaka shwasa presents with Ghurghuraka shwasa, Muhu teevra vega shwasa. Only Tamaka and Kshudra shwasa are curable or manageable, others are incurable. Hence Upashaya and Anupashaya are limited mainly to Tamaka and Kshudra shwasa. A detailed review of Nidana panchaka of above paves way for clear understanding of minute aspects connected to disease and aids in diagnosis and treatment with high precession.